Modeling a sustainable energy transition in northern Greenland: Qaanaaq case study. (December 2022) - Pantaleo, Alyssa; Albert, Mary R.; Snyder, Hunter T.; Doig, Stephen; Oshima, Toku; Hagelqvist, Niels Erik
Abstract: Many remote Indigenous communities in the high Arctic rely on diesel or other fossil fuels for their electricity generation, yet the high cost of the imported fuel limits households' ability to afford food and adequate housing and in turn, undercuts living conditions in the Arctic. While roughly 65% of energy generated by the Greenlandic utility company Nukissiorfiit comes from renewable sources, nearly 70% of public and private energy consumption for electricity and heat is fossil-fuel based Naalakkersuisut (2018) [1] . A transition to renewable energy achieved in partnership with the communities could strengthen local energy self-reliance and build technical capacity in ways that embrace their cultural heritage. This paper examines initial feasibility of the incorporation of solar energy for the hunting/fishing village of Qaanaaq, Greenland, a challenging environment where there is little wind or hydropower potential. Unit commitment optimization models are used to assess the feasibility of possible energy projects that include solar energy and energy storage in Qaanaaq's energy system, in hybrid systems with diesel generators. We also consider future energy system planning via electrified heat. We find that under a variety of economic conditions, solar and battery electric storage contribute to decreased costs to generate electricity in Qaanaaq. Currently, hydrogen storage is found to increase costs of energy in Qaanaaq, even considering future decreases in capital costs. However, green hydrogen may have positive impacts to the energy as a long-term energy planning strategy.